1988
DOI: 10.1351/pac198860111659
|View full text |Cite
|
Sign up to set email alerts
|

Lactone synthesis by electron transfer and radical chemistry

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
20
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Continuing our studies on the reactivity and stereochemical issues related to α-carbalkoxy radicals, we report herein examples of remarkably high stereoselectivity in 1,2-induction 2,3 and unprecedented 1,3-, 1,4-, and 1,5-asymmetric inductions in the free-radical C -allylation of α-acyl radicals derived from a series of N -substituted acyclic amino acid derivatives (Scheme 1), by exploiting intramolecular H-bonding as a stereocontrolling element.
…”
mentioning
confidence: 79%
“…Continuing our studies on the reactivity and stereochemical issues related to α-carbalkoxy radicals, we report herein examples of remarkably high stereoselectivity in 1,2-induction 2,3 and unprecedented 1,3-, 1,4-, and 1,5-asymmetric inductions in the free-radical C -allylation of α-acyl radicals derived from a series of N -substituted acyclic amino acid derivatives (Scheme 1), by exploiting intramolecular H-bonding as a stereocontrolling element.
…”
mentioning
confidence: 79%
“…We speculate that water can effectively decrease the barrier to rotation between the major Z -rotamer and minor E -rotamer which can cyclize (Scheme ) . Curran and Tamine have suggested that Z and E conformers of the radical are not sufficiently interconverting in benzene at 25 °C 6h. In water, however, the interconversion of the rotamers might occur as a result of the decrease of the barrier and cyclization from E -rotamer could afford lactone 2 .…”
mentioning
confidence: 94%
“…We chose an atom-transfer cyclization of allyl iodoacetate as a model reaction in water. The indirect bromoacetal method was developed by Stork and Ueno because direct cyclization of α-halo esters into γ-butyrolactones is a relatively slow radical reaction . Lactones are usually produced from this strategy by oxidation of the products prepared from radical cyclization of bromoacetal.…”
mentioning
confidence: 99%
“…It is also important to note that radical cyclizations of unconstrained esters such as 5 and 7 are quite rare, owing to the large barrier to rotation about the CO-0 bond which inhibits the formation of the proper conformer for cyclization. 8 The cyclization of the ketoester 8 (Scheme l), yielded a more complex product mixture. Photolysis of 8 generated a 60% yield of the cyclohexanone 12 and a 20% yield of the cyclopentanone 13 (ring methine coupling of 6 Hz).…”
mentioning
confidence: 99%